Arthur Ransome's Rewriting of the Russian Folktale Historicised. (3rd July 2016) - Bogrdanova, Tatiana
ABSTRACT: The young Arthur Ransome's Old Peter's Russian Tales (1916) that has today attained the status of a classic is of chief interest here as part of the British–Russian cultural interaction and interconnections at the turn of the twentieth century. In an attempt to historicise the author-translator in his creative effort to rewrite the Russian folktale, this paper focuses on his quest for magic and the collection of fairy stories, resulting from interacting with both place and people. A microscopic analysis of the translator's life and work in his early years in Russia, via a study of archival material (Brotherton Collections, University of Leeds Library) and other relevant documents, has helped to reconstruct them in a richness of detail that sheds light on the bigger picture of the British–Russian relationship. The translator's gift to his reader, a token of fruitful experiences in this new and exciting fairyland, was, in fact, the product of mediation agency between the two worlds, the role that Ransome had found crucial and realised successfully in practice. As a result, another cultural and emotional bridge was built to interconnect these two countries.